The Impact of Implementing Hybrid Learning on Flexibility and Quality of Learning - Syamsu Rijal; Zhang Wei; Deng Jiao; Yuanyuan Wang (Yayasan Adra Karima Hubbi, 2024)
Background:The implementation of hybrid learning is a learning method that refers to a learning method that combines or combines face-to-face and online-based learning. By implementing hybrid learning, it is possible for students who have limited infrastructure to study without coming to school. Research purposes:This research was conducted with the aim of determining the flexibility and quality of learning by implementing hybrid learning. Apart from that, it is also possible to find out about the learning experiences that have been produced through the hybrid learning process. Method:The method used in this research is a quantitative method.This method is a way of collecting numerical data that can be tested. Data was collected through distributing questionnaires addressed to students. Furthermore, the data that has been collected from the results of distributing the questionnaire will be accessible in Excel format which can then be processed using SPSS. Results:From the research results, it can be stated that the impact of implementing hybrid learning can help optimize the use of technology in education, so that learning materials can be developed that are more flexible and high quality, and teachers can choose appropriate teaching methods that suit student needs. Conclusion:From this research, it can be concluded that the impact of implementing hybrid learning can make it easier to carry out the learning process. Where the learning process is not only carried out face to face, but can be carried out online by utilizing existing technology